Financial Sector Regulation : Issues and Gaps. (Policy Papers; Policy Paper ;, 2004)
This paper addresses issues in financial sector regulation from two perspectives. First, it reports on the state of implementation of financial regulatory standards across banking, insurance, and securities sectors in a select group of Fund member countries. Second, it raises issues relating to the design of these three sector standards, arising from the implementation experience and the evolving structure of financial systems. In this regard, the paper identifies a few emerging regulatory risks and some cross-sectoral issues that may warrant further guidance by standard setters.